Anesthetic Management of a Pediatric Patient with Congenital Methemoglobinemia - Sung-Wook Choi; Elizabeth Putnam (Case Reports in Anesthesiology)
A 15-year-old girl with congenital methemoglobinemia and no prior anesthetic history presented for the extraction of multiple impacted molars. Pulse oximetry values were expected to complicate the accurate monitoring of her oxygenation status in the perioperative period. An arterial line was placed for hemodynamic monitoring, arterial blood gas (ABG) analysis, and obtaining the methemoglobin (MetHgb) level and additional blood gases if clinically indicated. A continuous CO-oximeter was also used. Her intraoperative course was uneventful and she was discharged home on the same day of the procedure. This report reviews this rare condition and describes the monitoring methods utilized to assess her oxygen and methemoglobin levels, as well as the anesthetic techniques and pharmacologic agents employed. With appropriate intraoperative monitoring and careful drug selection, pediatric patients with this unusual condition can safely undergo general anesthesia.